Jeruzsálem, Nebúkadreccar. Kritikai értelmiségi az ókori keleten a nemzeti és birodalmi politika erőterében - Komoróczy Géza, Jeremias (1985)
Jeremiah, Jerusalem, Nebuchadnezzar. A Critical Intellectual in the Ancient Near East in the Field of National and Imperial Politics.